Initial Results of Laparoscopic Proximal Gastrectomy With Double-tract Reconstruction Using Oblique Jejunogastrostomy Method on the Long-term Outcome of Postoperative Nutritional Status: A Propensity Score-matched Study. Issue 5 (October 2021) - Kimura, Kotaro; Ebihara, Yuma; Tanaka, Kimitaka; Nakanishi, Yoshitsugu; Asano, Toshimichi; Noji, Takehiro; Kurashima, Yo; Murakami, Soichi; Nakamura, Toru; Tsuchikawa, Takahiro; Okamura, Keisuke; Shichinohe, Toshiaki; et al.
Abstract : Background: The aim of this study was to evaluate the long-term nutritional state of patients with gastric cancer who underwent laparoscopic proximal gastrectomy with double-tract reconstruction (LPG-DTR) using oblique jejunogastrostomy method (OJG). Methods: Medical records of 38 patients who underwent LPG-DTR using OJG (21 patients) or laparoscopic total gastrectomy with Roux-en-Y reconstruction (LTG-RY) (17 patients) between October 2011 and March 2018 were retrospectively reviewed. In these patients, clinicopathologic variables were analyzed using propensity score matching for age, sex, body mass index, American Society of Anesthesiologists physical state, clinical stage, and lymph node dissection. Operative outcomes and postoperative nutritional status were compared between the 2 groups. Results: A total of 16 patients were matched to analyze the LPG-DTR and LTG-RY groups. The serum hemoglobin, total protein, and albumin levels at 12 months postoperatively ( P =0.008, 0.034, and 0.049) and serum hemoglobin level at 24 months ( P =0.025) in the LPG-DTR group was significantly superior to those in the LTG-RY group. Conclusions: The postoperative nutritional status as long-term outcomes of patients who underwent LPG-DTR using OJG was significantly superior to those who underwent LTG-RY. The results hereby presented suggest that LPG-DTR using OJG for gastric cancer produces better postoperative nutritional status.